New developments in the era of viral hepatitis vaccines - (:unkn) unknown (MARMARA UNIV, FAC MEDICINE, 2016)
Chronic hepatitis B and hepatitis C infections are major health problems in the world. Therefore, prevention of the transmission of the viral infections gets higher priority. Development of hepatitis B vaccines by recombinant technology provide higher prevention rates. However, this success could not be achieved with hepatitis C vaccine. The present review discusses recent developments for hepatitis B and C vaccines.
Keywords: New vaccines; Hepatitis B; Hepatitis C